Contribution of two different Na+ transport systems to acquired salinity tolerance in rice. (August 2020) - Sriskantharajah, Karthika; Osumi, Shota; Chuamnakthong, Sumana; Nampei, Mami; Amas, Junrey C.; Gregorio, Glenn B.; Ueda, Akihiro
Highlights: Rice varieties differ in their ability to acclimate to salinity stress. Acclimatized rice varieties exhibited 'Na + excluder' and 'Na + accumulator' characteristics in leaf Na + homeostasis. Acclimation treatment increased expression of the OsHKT1;5 or OsNHX1 gene in acclimatized varieties. Rice develops different mechanisms of salt acclimation using two Na + transport systems. Abstract: To elucidate the mechanisms of salt acclimation, physiological parameters of 70 rice varieties were compared under control and salt stress conditions after the acclimation treatment. The results indicated that some rice varieties had the ability to acclimatize to salt stress, exhibiting improved growth following the acclimation treatment under subsequent salinity stress compared to those without acclimation treatment. Conversely, some varieties exhibited reduced growth both with and without acclimation treatment under subsequent salinity stress. Acclimatized varieties had differential patterns of Na + accumulation in the leaf blades because some varieties reduced Na + accumulation under salinity stress, whereas others did not. Under salt stress, the acclimatized varieties with low Na + accumulation in the leaf blades highly induced the expression of the OsHKT1;5 gene in the roots, which may contribute to Na + exclusion from the shoots. On the other hand, the acclimatized varieties with high Na + accumulation in the leaf blades exhibited higher induction of the OsNHX1 gene, whose gene product participates in the compartmentalization of Na + into vacuoles. Thus, rice develops different mechanisms of salinity acclimation using two Na + transport systems, and active regulation of Na + transport at the transcription level may be involved in the salt acclimation process and enhance salinity tolerance.